The impact of online learning during the Covid-19 pandemic on learning outcomes - Budiman, Ridho Dedy Arief; Mlwale, Husna Juma; Syafruddin, Syafruddin; Hamka, Muh; Purnomo, Sigit (Yayasan Pendidikan Dan Pengembangan Harapan Ananda, 2024)
This study focuses on the impact of online learning during the Covid-19 pandemic on the learning outcomes of students in class XI Multimedia at SMK Negeri Hulu Gurung, Kapuas Hulu Regency. This study aims to analyze the implementation of online learning, its impact on students, and changes in learning outcomes during the pandemic. The research method used is a qualitative method with data collection techniques through observation, interviews, and documentation. The results showed that online learning caused a significant decline in student learning outcomes, where the average student absorption was below the 85% classical standard. This decline shows that although online learning has been implemented in accordance with the direction of the relevant agencies, constraints such as limited internet access and adaptation to new methods reduce the effectiveness of the learning process. This study suggests the need for regular evaluation and adjustment of learning methods to improve student learning outcomes in the future.